The effectiveness of Building Information Modelling (BIM) in solving railway project management issues in Malaysia - Molarn, M A; Ang, P S E; Ali, R B (IOP, 2024)
Railway projects involve complex planning and management as compared to regular construction projects, but BIM can simplify and improve the management of these projects. MRT 2 faced problems like design discrepancies and coordination issues, while Gemas - JB ETS encountered issues with construction changes, cost overruns, and project delays. Hence, this research intends to investigate the project management issues and examine the effectiveness of BIM implementation in solving project management issues in railway construction projects in Malaysia. A qualitative study was executed by conducting semi- structured interview on BIM professionals from the MRT 2 and Gemas-JB ETS railway construction projects. Six purposively selected respondents from the railway construction industry were interviewed, achieving data saturation. The main issues discovered were lack of communication, lack of coordination, clashes in construction, redesign and unrealistic schedules. The said issues mainly occurred during pre – construction stage. The level of BIM effectiveness in MRT 2 is high when full BIM was implemented as compared to Gemas – JB ETS that have low effectiveness when partial BIM was implemented. The findings of this study is able to show that full BIM implementation in a project management can greatly enhance coordination and efficiency while reducing costs in the railway industry.